Using triaxial accelerometry to detect hunts and kills by African wild dogs - Redcliffe, James; Creel, Scott; Goodheart, Ben; Reyes de Merkle, Johnathan; Matsushima, Stephani S.; Mungolo, Michelo; Kabwe, Ruth; Kaseketi, Emmanuel; Donald, Will; Kaluka, Adrian; Chifunte, Clive; Becker, Matthew S.; et al. (Frontiers in Ecology and Evolution, 2024)
Most large carnivores feed on prey infrequently and may expend large amounts of energy to locate, capture and kill their prey. This makes them probabilistically vulnerable to fluctuating rates of energy acquisition over time, especially within the increasingly human-altered landscapes that dominate their remaining range. Consequently, quantifying their hunting behaviors and success rates is critical, yet direct observation of these events is rarely feasible. We theorized that we could determine prey pursuit and capture in African wild dogs (Lycaon pictus) using a mechanistic approach by constructing Boolean algorithms applied to accelerometer data derived from collar-mounted tags. Here, we used this method and then iteratively improved algorithms by testing them on observed hunts and kills of collared packs. Using this approach on 47 days of acceleration from three wild dogs in three packs, we identified 29 hunts with 10 kills, all of which were confirmed by direct observation except for a single kill. Our results demonstrate that hunting effort and success can largely be determined from acceleration data using a mechanistic approach. This is particularly valuable when such behaviors are rarely quantified and offers a template for research on foraging in canid species, while also contributing to the expanding body of literature that employs similar methods to quantify hunting in large carnivores.